INCUBATOR BUSINESS IN A UNIVERSITY - Wajong, Andre M. R. (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Article discusses an incubator business in a university. From the research, it can be concluded that to manage an incubator is really obvious that the management should have an idea to create a business and make some profit. All the activity will be limited with the reality from the market. Because of that, the staff and management in the incubator have to have an attitude to be an entrepreneur.